2013
DOI: 10.1021/es303923w
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Heavy Metals by Submerged Macrophytes: Looking for Hyperaccumulators in Eutrophic Lakes

Abstract: To directly select submerged macrophytes with high accumulation capability from the field, 24 eutrophic lakes along the middle and lower reaches of the Yangtze River were investigated in the study. These eutrophic lakes have large amounts of heavy metals in both water and sediments because of human activities. The results showed that Najas marina is a hyperaccumulator of As and Cd, Ceratophyllum demersum is a hyperaccumulator of Co, Cr, and Fe, and Vallisneria natans is a hyperaccumulator of Pb. Strong positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 138 publications
(38 citation statements)
references
References 36 publications
0
35
1
1
Order By: Relevance
“…The Pb contents presented in this study were higher than most results in other studies, but the highest Pb content in V. natans was the same as previously reported. It has been reported that the Pb contents in V. natans were 2.80 mg/g in lakes (Xing et al, ) and 1.40 mg/g in experimental water (Wang et al, ). Xing et al () also reported that V. natans is a hyperaccumulator for Pb among 12 submerged macrophyte species in 24 eutrophic lakes (Xing et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The Pb contents presented in this study were higher than most results in other studies, but the highest Pb content in V. natans was the same as previously reported. It has been reported that the Pb contents in V. natans were 2.80 mg/g in lakes (Xing et al, ) and 1.40 mg/g in experimental water (Wang et al, ). Xing et al () also reported that V. natans is a hyperaccumulator for Pb among 12 submerged macrophyte species in 24 eutrophic lakes (Xing et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that the Pb contents in V. natans were 2.80 mg/g in lakes (Xing et al, ) and 1.40 mg/g in experimental water (Wang et al, ). Xing et al () also reported that V. natans is a hyperaccumulator for Pb among 12 submerged macrophyte species in 24 eutrophic lakes (Xing et al, ). The accumulations of Zn and Cu surpassed those reported before.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations